Identifying Comparison and Selection Criteria for Authentication Schemes and Methods - Velásquez, Ignacio (2017)
Multiple techniques exist for performing authentication such as text passwords and smart cards. Multi-factor authentication combines two or more of these techniques in order to enhance security. It is of interest to know what the current research on these authentication techniques is and what comparison and selection criteria exist that help in the decision of these techniques. A systematic literature review is performed in order to obtain the desired knowledge. Moreover, the found comparison and selection criteria are analyzed and organized in order to generate a list of criteria that can be used to help in the decision of authentication techniques in different situations. The results of this research help to cover the gap in literature that could be observed through literature, which is the lack of works that focus on the comparison and selection of authentication techniques.